2008
DOI: 10.2190/hs.38.1.c
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Differential Mortality by Educational Attainment in Adults in the United States

Abstract: Economic inequality has increased substantially in the United States since the early 1970s. Inequality in mortality increased from 1960 to 1986. To assess the trend in inequality in mortality the authors calculate age-adjusted mortality rates by educational attainment for 2000 and compare them with rates from 1960 and 1986, using relative and absolute indexes of inequality. Rates are calculated for non-Hispanic white and black adults aged 25 to 64 years, using mortality data from U.S. Vital Statistics and popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…These differential trends that were more favorable to the most educated population resulted in increasing relative disparities between the most and least educated groups from 1993 through 2007. These findings add to previous reports that documented widening socioeconomic disparities in mortality since the 1960s [3][10]. Similar to our results, the middle-course assessment of U.S.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These differential trends that were more favorable to the most educated population resulted in increasing relative disparities between the most and least educated groups from 1993 through 2007. These findings add to previous reports that documented widening socioeconomic disparities in mortality since the 1960s [3][10]. Similar to our results, the middle-course assessment of U.S.…”
Section: Discussionsupporting
confidence: 92%
“…), race/ethnicity, residence, sex, and sexual orientation has been an overarching goal of the decennial Department of Health and Human Services' Healthy People Initiative, which began in 1979 [1], [2]. Previous studies that have examined temporal trends in mortality disparities by socioeconomic status found widening rather than narrowing of the disparities [3][10]. In our previous report, we investigated individual-level socioeconomic disparities in mortality using national vital statistics and noted increasing educational disparities from 1993 through 2001 for all-cause and several major causes of death in both men and women [11].…”
Section: Introductionmentioning
confidence: 99%
“…Higher socioeconomic status has been shown to have beneficial effects on health resulting from several mechanisms such as the adoption of healthier lifestyles, better ability to cope with stress, and more quality medical care to effectively management chronic diseases (Hayward, Hummer, & Sasson, 2015). In the U.S., for example, there is ample evidence suggesting increasing survival inequalities by education (Hadden & Rockswold, 2008; Hayward et al, 2015; Montez, Hummer, & Hayward, 2012; Olshansky et al, 2012), and that these differences appear to be so systematic and permissive that they can be seen at the regional and county level (Kulkarni, Levin-Rector, Ezzati, & Murray, 2011; Murray, Kulkarni, & Ezzati, 2005; Sheehan, Montez, & Sasson, 2018). For example, a recent study linking educational attainment and adult mortality in the U.S. population shows that the growing mortality advantage of people with more education is a recent phenomenon that emerged at the end of the 20th Century and beginning of this century (Hayward et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown a significant increase in mortality and life expectancy differentials across education groups (Meara et al, 2008;Hadden and Rockswold, 2008). Also, Waldron (2007) found compelling evidence of increases in differential mortality for men aged 60 and older using mortality data covering the period 1972 to 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Meara et al (2008), using data from the National Longitudinal Mortality Study that spans 1981 to 1988 and 1991 to 1998, as well as census population estimates matched to death certificated data for years 1990 and 2000, found that with the exception of black males, all recent gains in life expectancy at age 25 have favored individuals with some college or more education, raising educational differentials by 30 percent. Similarly, Hadden and Rockswold (2008), matching U.S. Vital Statistics and population estimates for individuals ages 25 to 64 in 2000, found significant increases in relative and absolute indices of mortality inequality by education groups compared to estimates from 1986, especially for men and white individuals.…”
Section: Introductionmentioning
confidence: 96%